Analisis Perilaku Tanggung Jawab Dalam Pembelajaran PPKN Siswa Kelas IV SD Negeri Bunder IV Kabupaten Tangerang - Prahastiwi, Windar; Sa’odah, Sa’odah; Nurfadhillah, Septy (Jurnal Ilmiah Wahana Pendidikan, 2024)
This study aims to determine students' responsible behavior in Civics lessons. This research is a descriptive qualitative research by taking data at SD Negeri Bunder 4, Tangerang Regency. Data analysis is done by collecting data, presenting data that draws conclusions. The results showed that the analysis of responsible behavior in Civics lessons at SD Negeri Bunder 4 Tangerang Regency, namely from the data collection carried out through observation, interviews, and documentation that: Analysis of responsible behavior in Civics learning students are already responsible in learning and behavior, this can be seen that students have carried out their obligations and responsibilities properly.